Strengthening the Indigenousization of Islam by Gus Dur in the Middle of the Formalization of Religion - Siswoyo Aris Munandar; Siti Muliana; Jazilus Sakhok (Universitas Islam Negeri Sunan Kalijaga, 2020)
The focus of this article is to examine the process of Gus Dur's indigenousization of Islam as a response to the increasing phenomenon of religious formalization. This topic is considered important because it is an effort to keep local culture and traditions down to earth. Apart from that, the indigenousization of Islam is also a contra-naration against the conservative understanding of Islam which states that indigenous Islamic rituals are regarded as bid’ah, shirk or khurafat that must be rejected. This was raised because according to muslim fundamentalists, the religious practices of indigenous Muslims are opposite of the practices of salaf as-salih which conform Islam totality or kaffah and authentic Islam. In addition, the indigenousization of Islam emerged as a response to the phenomenon of the formalization of religion which leads to the commodification of religion by making religion as a sale value. This writing employes socio-descriptive method which has come to conclusions as follows. First, the indigenousization of Islam which was initiated by Gus Dur was the result of Gus Dur's long struggle with praxis in nature. Second, Arabization with its’ formalization of religion has injured the diversity of the nation of the archipelago and opened up opportunities for the rise of ideological and political interests. Third, the common thread or root of the problem between conservative Islamic groups with their attitudes of formalizing religion and the indigenousization of Islam lies in the differences in understanding the values of Islamic normativity and culture.